Synthesis, Characterization, and Stability Evaluation of β-Carotene Encapsulated in Starch-Chitosan/Tripolyphosphate Matrices - Agnes Dyah Novitasari Lestari; Dwi Siswanta; Ronny Martien; Mudasir Mudasir (Indonesian Journal of Chemistry, 2020)
This study aims to investigate the synthesis and characterization of β-carotene encapsulated in the blending matrices of starch (native and hydrolyzed starch)-chitosan/TPP (tripolyphosphate) by examining the effects of starch-to-chitosan weight ratio, β-carotene addition level, and TPP addition level on the encapsulation efficiency (EE) and loading capacity (LC); and to evaluate their storage stability. The encapsulation was done by the dropwise addition of ethanolic β-carotene dispersion into the blending matrices. The results of XRD analysis show that the encapsulation process significantly decreases the crystallinity of the starches, chitosan, and β-carotene. Scanning electron microscope (SEM) images reveal that the encapsulation products form irregular lumps. The EE and LC tend to increase with the increase in polymer fraction of matrices and β-carotene addition level, and with the decrease in TPP addition level. The addition of chitosan and the replacement of native starch by hydrolyzed starch tend to increase storage stability of β-carotene encapsulated in the starch matrix because chitosan can act as a good film-forming and antioxidant, while hydrolyzed starch contains amylose amylopectin with a short chain which is better in film-forming ability. These results promote the use of the hydrolyzed starch-chitosan/TPP as a matrix to enhance the stability β-carotene via encapsulations.